Longitudinal Trends in U.S. Drug Shortages for Medications Used in Emergency Departments (2001–2014). (30th December 2015) - Hawley, Kristy L.; Mazer‐Amirshahi, Maryann; Zocchi, Mark S.; Fox, Erin R.; Pines, Jesse M.
Abstract: Objectives: This was a study of longitudinal trends in U.S. drug shortages within the scope of emergency medicine (EM) practice from 2001 to 2014. Methods: Drug shortage data from the University of Utah Drug Information Service were analyzed from January 2001 to March 2014. Two board‐certified emergency physicians classified drug shortages based on whether they were within the scope of EM practice, whether they are used for lifesaving interventions or high‐acuity conditions, and whether a substitute for the drug exists for its routine use in emergency care. Trends in the length of shortages for drugs used in EM practice were described using standard descriptive statistics and regression analyses. Results: Of the 1, 798 drug shortages over the approximately 13‐year period (159 months), 610 shortages (33.9%) were classified as within the scope of EM practice. Of those, 321 (52.6%) were for drugs used as lifesaving interventions or for high‐acuity conditions, and of those, 32 (10.0%) were for drugs with no available substitute. The prevalence of EM drug shortages fell from 2002 to 2007; however, between January 2008 and March 2014, the number of EM drug shortages sharply increased by 435% from 23 to 123. From January 2008 to March 2014 shortages in drugs used as a direct lifesaving intervention or for high‐acuity conditions increased 393% from 14 to 69, and shortages for drugs with no available substitute grew 125% from four to nine. Almost half (46.6%) of all EM drug shortages were caused by unknown reasons (the manufacturer did not cite a specific reason when contacted). Infectious disease drugs were the most common EM drugs on shortage, with 148 drug shortages totaling 2, 213 months during the study period. Conclusions: Drug shortages impacting emergency care have grown dramatically since 2008. The majority of shortages are for drugs used for lifesaving interventions or high‐acuity conditions. For some, no substitute is available.